PCSK9 inhibitors ameliorate arterial stiffness in ACS patients: evidences from Mendelian randomization, a retrospective study and basic experiments - Xu, Linghao; Wang, Liang; Wang, Yuanqi; Wang, Yiqiong; Jiang, Yuanzhen; Du, Peizhao; Cheng, Jing; Zhang, Chunsheng; Wang, Ruijie; Jiao, Tiantian; Xing, Lijian; Ma, Jiangping; et al. (Frontiers in Medicine, 2024)
Background Current evidences suggest that Proprotein Convertase Subtilisin/kexin Type 9 inhibitors (PCSK9i) exhibit a protective influence on acute coronary syndrome (ACS). Nevertheless, further investigation is required to comprehend the impact and mechanisms of these pharmaceutical agents on inflammatory factors and arterial stiffness (AS) in patients with ACS. Consequently, the objective of this study is to ascertain the influence of PCSK9i on arterial stiffness in ACS patients and elucidate the underlying mechanisms behind their actions. Methods This study employed Mendelian randomization (MR) analysis to examine the association between genetic prediction of PCSK9 inhibition and arterial stiffness. Data of 71 patients with ACS were retrospectively collected, including PCSK9i group (n = 36, PCSK9 inhibitors combined with statins) and control group (n = 35, statins only). Blood lipid levels, inflammatory markers and pulse wave velocity (PWV) data were collected before treatment and at 1 and 6 months after treatment for analysis. Additionally, cell experiments were conducted to investigate the impact of PCSK9i on osteogenesis of vascular smooth muscle cells (VSMCs), utilizing western blot (WB), enzyme-linked immunosorbent assay (ELISA), and calcification index measurements. Results The results of the MR analysis suggest that genetic prediction of PCSK9 inhibition has potential to reduce the PWV. Following treatment of statins combined with PCSK9 inhibitors for 1 and 6 months, the PCSK9i group exhibited significantly lower levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), C-reactive protein (CRP), interleukin-6 (IL-6), fibrinogen (FIB) and procalcitonin (PCT) compared to the control group (p < 0.05). Additionally, PWV in the PCSK9i group demonstrated significant reduction after 6 months of treatment and was found to be associated with the circulating CRP level. In cell experiments, PCSK9i pretreatment ameliorated osteogenesis of VSMCs through reducing the deposition of calcium ions, alkaline phosphatase (ALP) activity, and expression of runt-related transcription factor 2 (RUNX2). Conclusion PCSK9i have potential to enhance arterial stiffness in ACS patients. Specifically, at the clinical level, this impact may be attributed to alterations in circulating CRP levels. At the cellular level, it is associated with the signaling pathway linked to RUNX2.